ANALISIS FINANSIAL UMKM KOPI CILIBUR DI KABUPATEN BREBES - Khusnul Khatimah; Sarah Ghania; Viyolanda Azrimultiya (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Coffee has great potential as a leading plantation commodity in Indonesia. The highlands in Brebes Regency, specifically in Cilibur Village, have been used by farmers who collaborate with Perhutani to open land for Arabica coffee plantations. Since 2018, Mr. Muzayin has utilized the potential and opportunities in the coffee market, which are quite high, to process coffee beans into ground coffee with the Kopi Cilibur brand. The research aims to estimate business costs, revenues and profits from the Cilibur Coffee business. Data collection was carried out in March-October 2023. The analytical method used was cost, revenue and business profit analysis. The results of the research showed that the total cost of the Cilibur Coffee business was IDR 356,620/production with a revenue value of IDR 600,000/production. The profit value of the Cilibur Coffee business was IDR 243.380/production. The business analysis is intended so that Cilibur Coffee products can find out the actual total costs so that they can re-estimate the price basic products to create competitive prices Keywords: Fiancial, Bussiness, Cost, Profit Abstrak Kopi memiliki potensi yang besar sebagai komoditas perkebunan unggulan di Indonesia. Dataran tinggi di Kabupaten Brebes tepatnya di Desa Cilibur telah dimanfaatkan oleh petani yang bekerjasama dengan Perhutani untuk membuka lahan perkebunan kopi jenis arabika. Potensi dan peluang pasar kopi yang cukup tinggi sejak tahun 2018 dimanfaatkan oleh Bapak Muzayin untuk mengolah biji kopi menjadi kopi bubuk bermerek Kopi Cilibur. Penelitian bertujuan untuk mengestimasi biaya usaha, penerimaan, dan keuntungan usaha Kopi Cilibur. Pengambilan data dilakukan pada Bulan Oktober 2023. Metode analisis yang digunakan analisis biaya, penerimaan, dan keuntungan usaha. Hasil penelitian diperoleh biaya total usaha Kopi Cilibur sebesar Rp356.620/produksi dengan nilai penerimaan Rp600.000/produksi. Nilai keuntungan usaha Kopi Cilibur sebesar Rp243.380/produksi. Analisis usaha dimaksud agar produk Kopi Cilibur dapat mengetahui biaya total yang sebetulnya sehingga dapat mengestimasi kembali harga pokok produk (HPP) supaya terbentuk harga kompetitif. Kata kunci: Finansial, Usaha Biaya, Keuntungan